Optical Properties of Electrically Active Gold Nanoisland Films Enabled with Interfaced Liquid Crystals - Yen, Hung-Chi (Nanomaterials (Basel), 2020)
A system comprising a gold nanoisland film (Au NIF) covered with a liquid crystal (LC) material is introduced. By applying a voltage across the LC bulk, we demonstrate that changes in the refractive-index and orientation significantly modified the hybrid plasmonic–photonic resonances of the Au NIF. The hybrid structure enabled active control of the spectrum of the resonance wavelength of the metallic nanoisland by means of an externally applied electric field. Our modeling supports the observed results in LC/Au NIF. In a combination of the nanostructured surface with birefringent LCs, nonpolarized wavelength tunability of ~15 nm and absorbance tunability of ~0.024 were achieved in the visible wavelength, opening the door to optical devices and nanoscale sensors.